PENGARUH KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP KEPUASAN NASABAH PD BANK PERKREDITAN RAKYAT KANTOR KAS (Faletehan Jurnal Ekonomi dan Bisnis, 2022)
This research was conducted to determine the effect of service quality and product qualitypartially or simultaneously on customer satisfaction of PD Bank Perkreditan Rakyat, Rau CashOffice, Serang City. This type of research is a quantitative survey, with data collectiontechniques through primary data in the form of observations and questionnaires.The results of the analysis show that service quality has a positive effect on customersatisfaction by 0.398 and the results of the partial t test are obtained with a tcount greater thanttable (4779 > 1.984) with sig. 0.00 < 0.05 so that H0 is rejected and Ha is accepted. Theresults of the analysis show that product quality has a positive effect on customer satisfaction of0.697 and the results of the partial t test are obtained with a tcount greater than ttable(8.190>1.984) with sig. 0.00 < 0.05 so that H0 is rejected and Ha is accepted. The results ofthe analysis show that the value of Fcount>Ftable (132.279>3.19) and the value of sig F <(0.00<0.05). So it can be concluded that Ho is rejected and Ha is accepted, so that there is aneffect of service quality and product quality together on customer satisfaction of PD BankPerkreditan Rakyat, Rau Cash Office, Serang City. As much as 75.2% that customersatisfaction is explained by the variables of service quality and product quality.